59 Effects of exogenous glucocorticoid administration on leptin concentrations in perinatal dairy bull calves. (28th November 2020) - Morris, Camille; McCarty, Keelee J; Long, Nathan
Abstract: Previous studies suggest a relationship between leptin and cortisol immediately postpartum is linked to improved feedlot efficiency on cattle exposed to perinatal stressors. The objective of the current study was to determine the effects of exogenous cortisol administration on circulating leptin concentrations in perinatal dairy bull calves. Within four hours of parturition, Holstein bull calves were randomly assigned to treatments and intravenously infused with low cortisol (LC; n = 9, 3.5 ug/kg of cortisol), high cortisol (HC; n = 9, 7.0 ug/kg of cortisol), or a sham infusion control (CON; n = 9, similar volume of saline). Calves were housed similarly and fed milk replacer (28% CP, 20% fat) three times daily. Blood collections were performed via jugular venipuncture using Z/9mL serum collection tubes (Sarstedt, Newton, NC) from d 0 to 5 of age. Serum samples were incubated for 1 h at room temperature then overnight at 4°C, centrifuged at 1800 x g at 4°C for 20 minutes, serum decanted, and stored long term at -20°C until analysis. At 5 d of age, calves were euthanized utilizing an overdose of sodium pentobarbital (Schering-Plough Animal Health, Union, NJ) and cerebral-spinal fluid (CSF) from the third ventricle of the brain was collected and stored at -80°C until analysis. All samples were analyzed for leptin concentrations via a previously-validated radioimmunoassay. Serum leptin concentrations were analyzed via repeated measures of ANOVA and CSF leptin concentrations via the GLM procedure of SAS (SAS Institute Inc., Cary, NC, USA). Serum leptin concentrations of HC and LC were decreased (P = 0.013) compared to CON, and d 0 was decreased (P < 0.001) compared to all other days of age. Cerebral-spinal fluid leptin concentrations of HC and LC were decreased (P = 0.005) compared to CON. In summary, exogenous cortisol administered to perinatal dairy bull calves reduced leptin concentrations in serum and CSF.